Evaluasi Pendidikan Dalam Surah Al-Baqarah Ayat 31-34 Analisis Tafsir Ath-Thabari - Aufi Nadra Izzati; Dedi Masri; Rahmad Nasution; Audiva Azzahra; Meida Sari Siregar (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study explains the educational evaluation contained in surah Al-Baqarah 31-34 based on the interpretation of Ath-Tabari. The type of research used is descriptive qualitative. Data collection techniques were taken from various sources, both books, journals and relevant articles. The results of this study indicate that the evaluation of education contained in surah Al-Baqarah 31-34 is based on the analysis of the interpretation of Ath-Tabari, namely there are 3 processes carried out in providing evaluation including listening, explaining, and producing evaluations. Evaluation is very important for today's education, to find out the development or changes that students have both from the affective aspect, cognitive aspect, and psychomorphic aspect.